2016
DOI: 10.5301/jva.5000629
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of two different approaches for ultrasound-guided internal jugular vein cannulation in hemodialysis patients

Abstract: In our experience AOP and LIP approaches have shown the same outcomes. However, we believe that the LIP technique has potential benefits and it should be considered in the decision process of IJV cannulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…The use of ultrasound in venous canalization avoids these complications and facilitates catheter placement. 1,[15][16][17][18][19][20] In the Cochrane review with meta-analysis by Rabindranath et al, 21,22 they found that ultrasound-guided placement of the jugular and femoral venous accesses presented better clinical and technical results than puncture guided by anatomical marks, and with fewer complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of ultrasound in venous canalization avoids these complications and facilitates catheter placement. 1,[15][16][17][18][19][20] In the Cochrane review with meta-analysis by Rabindranath et al, 21,22 they found that ultrasound-guided placement of the jugular and femoral venous accesses presented better clinical and technical results than puncture guided by anatomical marks, and with fewer complications.…”
Section: Discussionmentioning
confidence: 99%
“…The complications that arise during CVC placement are mainly due to anatomical characteristics, unrecognized stenosis, and venous thrombosis; identification via anatomical marks is not possible. The use of ultrasound in venous canalization avoids these complications and facilitates catheter placement 1,15–20 . In the Cochrane review with meta‐analysis by Rabindranath et al, 21,22 they found that ultrasound‐guided placement of the jugular and femoral venous accesses presented better clinical and technical results than puncture guided by anatomical marks, and with fewer complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, in-plane needle insertion permits a very precise control of needle advancement diminishing the chance of mechanical complications. 22,23 Unlike classical infra-clavicular subclavian vein cannulation, with a supraclavicular approach the guidewire is directed downwards into the vessel and toward the superior vena cava which can minimize the chance of guidewire and catheter malposition. Also, the supraclavicular area can be externally compressed to attain hemostasia in patients with coagulopathy and increased bleeding risk.…”
Section: Discussionmentioning
confidence: 99%
“…Por la técnica a través de parámetros anatómicos esta complicación es baja (1 al 2,4%) e incluso, estudios similares, (13,15,(18)(19) también reportan ausencia completa de esta complicación con el uso de guía ecográfica En relación a la medición del éxito se obtuvo un 100% en el grupo con ecografía y 94,6% en el grupo sin ecografía, resultando una diferencia sin significancia estadística. En contraste con estudios similares publicados, estos valores se encuentran acordes a otros reportes donde la efectividad va del (15,(20)(21)(22)(23)(24) 87% al 89% en el grupo sin guía ecográfica y del 97% al 100% con guía ecográfica En los tres casos de fracaso por parámetros anatómicos, la vía fue recolocada con éxito bajo guía ecográfica en un segundo tiempo, sin realizar registro de los mismos.…”
Section: Discussionunclassified